2013
DOI: 10.1097/ico.0b013e318242fd0f
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Central Corneal Thickness Using Fourier-Domain Optical Coherence Tomography Versus Ultrasound Pachymetry in Primary Open-Angle Glaucoma

Abstract: FD-OCT underestimates CCT compared with CCT measured by USP in POAG. Although highly correlated, the difference between these 2 devices can be clinically significant in the context of refractive surgeries in POAG patients but not in intraocular pressure estimation. This difference also seems to be independent of the number of antiglaucoma treatments used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 29 publications
2
11
1
3
Order By: Relevance
“…18 Similarly, it was reported that RTVue OCT underestimated CCT compared with CCT measured by UP in patients with primary open-angle glaucoma. 10 Shammas et al reported that precision of the measurements obtained by the Lenstar was extremely high. 8 The CCT measurements obtained by Lenstar noncontact biometry have been correlated with the results of UP.…”
Section: Discussionmentioning
confidence: 99%
“…18 Similarly, it was reported that RTVue OCT underestimated CCT compared with CCT measured by UP in patients with primary open-angle glaucoma. 10 Shammas et al reported that precision of the measurements obtained by the Lenstar was extremely high. 8 The CCT measurements obtained by Lenstar noncontact biometry have been correlated with the results of UP.…”
Section: Discussionmentioning
confidence: 99%
“…Specular microscopy (e.g., Topcon SP-3000P, Topcon Corporation, Tokyo, Japan), optical coherence tomography, rotating Scheimpflug camera (e.g., Pentacam, Oculus Inc., Wetzlar, Germany), optical low-coherence reflectometry (e.g., Lenstar, Haag-Streit AG, Koeniz, Switzerland), and slitscanning optical pachymetry (OPT; e.g., Orbscan, Bausch & Lomb, Rochester, NY, USA) are other imaging techniques that are non-contact. Results from these OPT techniques are not interchangeable between devices and differ significantly compared with UP [1][2][3][4][5]; some devices overestimate [5,6], while others underestimate [4,7]. The presence of corneal haze and keratoconus may explain some differences in the measurements between devices [8,9].…”
Section: Cct Measurementmentioning
confidence: 99%
“…Previous reports have shown that OCT gives lower CCT readings compared to ultrasound 4749. The opposite, overestimation with OCT compared to USP has also been reported 50,51.…”
Section: Discussionmentioning
confidence: 78%
“…Wells et al48 compared optical pachymetry, OCT and ultrasound, and found that these devices are not interchangeable in clinical practice. Garcia-Medina et al49 compared Fourier-Domain OCT with USP in 80 patients with POAG and found a significant difference between the mean CCT. However, they indicated that this difference should not be clinically significant in IOP estimation.…”
Section: Discussionmentioning
confidence: 99%